Fotograf Noam Griegst - Et kig gennem linsen - Blüdnikow, Bent; Zoref, Katrine Hassenkam (Rambam. Tidsskrift for jødisk kultur og forskning, 2014)
Noam Griegst - A Look Through the Lens Noam Griegst is a fashion photographer and one of the best in the industry. He grew up in an artistic home with parents who designed jewelleries and porcelain. Noam Griegst knew from an early age that he wanted to work in photography, and after high school he worked as an apprentice for a Danish documentary photographer. After some years, he left for Paris where he worked as a freelance photographer for a number of Danish newspapers. He has since then worked all over the world, shooting pictures for the fashion industry, and only in recent years he has seriously invested in more personal projects. One of his ambitious projects was his collaboration with the Royal Danish Ballet, where he spent eighteen months photographing dancers. Rambam is delighted to bring a series of Noam Griegst’s photos, showing the diversity of this Danish Jewish photographer.